Англи хэлний угтвар үгийн бүтэц-үүргийн тогтолцоо: The Structural-Functional system of English Prepositions - Ц., Отгонсүрэн (Mongolian Studies, 2023)
The preposition is one of the most problematic units in English Grammar. As structure, it has three types of formations: 1. The Simple Preposition, which includes single words like in, on, under, above, near, etc; 2. The Complex Preposition, formed by two or more words like according to, because of, on account of. in accordance with, etc; and 3. The Marginal Preposition, derived from verb with present or past participles like concerning, considering, compared, given, etc. According to our research, there are five alternative functions, namely: 1. To denote the relation between words or phrases in any sentence; 2. To truncate any adjective clauses with prepositional phrase; 3. To link a subordinate clause to the main clause; 4. To be a particle of phrasal verb; 5. To determine any approximate numeral or measure. The simple prepositions are quite abstract and more frequent in sentence, which bring all the functions above mentioned. The complex ones perform the function of linking noun phrase or subordinate clause to main clause, while the marginal prepositions are used as the simple ones.